Response to Dettmers et al. (2012): Great Lakes Fisheries Managers Are Pursuing Appropriate Goals. Issue 3 (21st March 2014) - Claramunt, Randall M.; Clapp, David F.
ABSTRACT: After reading the article by Dettmers et al. in the November 2012 issue of Fisheries ("Management of Alewife Using Pacific Salmon in the Great Lakes: Whether to Manage for Economics or the Ecosystem?"), we feel compelled to respond and to present a different perspective on this important management issue. Despite the generally positive contribution to Great Lakes literature made by this article, it contains several inaccuracies concerning the past and current state of Great Lakes ecosystems. Dettmers et al. present an oversimplification of options currently available to Great Lakes fisheries managers; a false dichotomy describing only two future options for management of these fisheries. We submit that managers could strive to "… maintain a diverse salmonid community, [while proceeding] (to the extent possible) with native species rehabilitation" and we conclude that, "… on each of the Great Lakes, managers are pursuing appropriate goals, managing the aquatic resources of the lakes for the greatest public good, given the variability in conditions and likelihood for success specific to each lake."